CAPABILITY OF WATER AND ETHYL ACETATE FRACTIONS OF BENALU (Dendrophthoe L.f Ettingsh) LEAVES TO DISSOLVE CALCIUM KIDNEY STONE IN VITRO, DETERMINED USING FAST NEUTRON ACTIVATION METHOD - ., Sasmito; ., Darsono; Kamal, Zainul; Kristanto, Joko (Indonesian Journal of Pharmacy, 2001)
Kidney stone disease is the second major causal leading to kidney failure. Treatment to the disease could be by surgery, ultravibration and either traditional or modern medecines. Dendrophthoe falcata (L.f) Ettingsh grow, as a parasite, on the mindi (Melia azeradach), a plant has yet been used to cure kidney disorder caused by calcium kidney stone. Dendrophthoe falcata (L.f) Ettingsh leaves powder was extracted by ethanol (70%) and re-extracted by ethyl acetate. The compound content in water and ethyl acetate fractions were analyzed by thin layer chromatography (TLC) using cellulose as the stationary phase and a mixture of butanol: acetic acid: water (4:1:5) as mobile phase. The TLC data showed that water and ethyl acetate fractions contained flavonoid compounds. Kidney stone was analyzed using Infra Red Spectrophotometer to identify its chemical contents. The result showed that the kidney stone consisted of calcium and magnesium carbonate/phosphate. The Fast Neutron Activation analysis was utilized to determine the solubility of kidney stone. The result exhibited that the maximum solubility of kidney stone was achieved in water fraction with the concentration of 20 % or in ethyl acetate fraction with the concentration of 40 %. The solubility of kidney stone in water fraction was higher than that in ethyl acetate fraction.Key word : Kidney stone , Dendrophthoe falcata , Water fraction, Ethyl acetat fraction.